ANALISIS KEBIJAKAN DAN DINAMIKA KERJASAMA KAWASAN EKONOMI BIRU INDONESIA DALAM KERANGKA KERJA ASEAN - Soraya Ayumara; Amir Mukadar (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
The blue economy has become a strategic agenda for ASEAN countries in an effort to achieve sustainable economic growth based on the management of marine resources. Indonesia, as the world's largest archipelagic country with the second longest coastline globally, has a central role in encouraging the implementation of the ASEAN Blue Economy Framework. This article analyzes Indonesia's blue economy policy in the context of ASEAN regional cooperation, identifies the dynamics of the implementation of the regional framework, and examines the challenges and opportunities faced. Through the method of document analysis and literature on national and regional policies, this study finds that Indonesia has played a proactive role as the driving force of the ASEAN blue economy through the launch of the Indonesia Blue Economy Roadmap 2023-2045 which is a reference for other ASEAN countries. However, implementation at the national and regional levels still faces a variety of structural barriers, including capacity gaps between countries, funding limitations, and the need for harmonization of cross-border regulations. This article provides recommendations to strengthen national-regional policy synergies, enhance innovative financing mechanisms such as blue carbon finance, and strengthen the role of coastal communities in decision-making. Keywords: blue economy, ASEAN, Indonesia, maritime policy, regional cooperation, sustainable development